Constraints on the Tectonic Setting of the Andaman Ophiolites, Bay of Bengal, India, from SHRIMP U-Pb Zircon Geochronology of Plagiogranite - Sarma, D; Jafri, S.; Fletcher, Ian; McNaughton, Neal (University of Chicago, 2010)
The Andaman ophiolites are well exposed in the Andaman group of islands, which is part of the Sunda-Burmesedouble-chain arc system in the Bay of Bengal, India. Plagiogranites occurring on the eastern margin of the southernpart of South Andaman Island appear as interstitial vermicular and micrographic intergrowths of quartz and plagioclase.They are tonalitic to trondhjemitic in composition, and their Rb, Yb, Ta, and Y abundances are characteristicof a volcanic-arc affinity. Sensitive high-resolution ion microprobe U-Pb dating of zircons from a plagiogranite withinthe Andaman ophiolite has yielded a weighted mean 206Pb/238U age of 93.61.3 Ma, interpreted as the age of itscrystallization. The subduction-related plagiogranite has intruded a gabbro unit of the Andaman ophiolites as wellas extrusives of the East Coast Volcanics at this time. Since the Andaman ophiolitic rocks predate the plagiogranite,they cannot have been generated in the currently active Late Miocene Andaman-Java subduction zone and were mostlikely obducted onto the leading edge of the Eurasian continent at an earlier phase of subduction activity during earlyCretaceous time.